Aerogelic light: Art & science research on the ethereal nanomaterial silica aerogel, for sustainable urban design - Michaloudis, Ioannis; Green, M. (International Society for the Advancement of Supercritical Fluids, 2012)
This paper aims to present Aerogels as materials that can be considered as sustainable works of art & design as well as concepts for sustainable urban design. Typically, aerogels are amongst the world’s lightest solids and have some of the best insulation qualities known to man. These inherent material characteristics make them important candidates in future urban ecological strategies. These physical properties are as pivotal to an environmental awareness as the aesthetic properties embodied in aerogels. In combining art and science, these works have the ability to visually represent our surrounding natural world in a unique, aerogelic way. A cosmic material that is almost immaterial, we merge two words here, ‘angel’ and ‘aerogel’ to reference the ethereal and the unseen. Sustainable urban design is at the forefront of international discussion, as the issues of changing weather patterns, arctic shelf ice depletion and global warming (amongst other topics) has reinvigorated dialogue on the subject. Materials that have the ability to withstand acute temperatures or to insulate – both of which are inherent properties of aerogel – are currently in high demand - the extreme insulation properties inherent in silica aerogels have wide ranging possibilities, from architectural applications to garment design within the fashion industry. We seek to present aerogels as materials that not only inform us about the world around us, but also to help create a sustainable future, opening new avenues for dialogue, specifically in regards to green design.